2007
DOI: 10.1590/s1679-87592007000400004
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic nutrient pollution of coral reefs in Southern Bahia, Brazil

Abstract: Spatial, temporal and anthropogenic controls on nutrient distribution were evaluated for nearshore and offshore reefs at Porto Seguro Bay, Southern Bahia. Water samples were analysed for total oxidised nitrogen (TON), soluble reactive phosphorus (SRP), reactive silica (DSi), and chlorophyll a (Chl). The results indicate that rainfall promotes a significant (F=19.873, p<0.001) increase in the load of nutrients to nearshore (average 12% increase) and offshore reefs (average 31% increase). Nutrient concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
2
5
0
2
Order By: Relevance
“…It also showed a significant positive correlation with turbidity (r=0.63), indicating fluvial source, with higher values near the mouth of the river, decreasing towards the East. The values obtained in this study were similar to those observed by Koening and Macêdo (1999), with a variation of 1.42 µmol L -1 to 10.71 µmol L -1 in Itamaracá (State of Pernambuco), and those observed by of Costa (2007) that showed a variation from 2.13 µmol L -1 to 11.47 µmol L -1 in Porto Seguro (State of Bahia). They also noted a decrease in nutrient concentrations, increasing with the distance from the coast.…”
Section: T (°C)supporting
confidence: 89%
“…It also showed a significant positive correlation with turbidity (r=0.63), indicating fluvial source, with higher values near the mouth of the river, decreasing towards the East. The values obtained in this study were similar to those observed by Koening and Macêdo (1999), with a variation of 1.42 µmol L -1 to 10.71 µmol L -1 in Itamaracá (State of Pernambuco), and those observed by of Costa (2007) that showed a variation from 2.13 µmol L -1 to 11.47 µmol L -1 in Porto Seguro (State of Bahia). They also noted a decrease in nutrient concentrations, increasing with the distance from the coast.…”
Section: T (°C)supporting
confidence: 89%
“…2008), nutrification of coastal environments (Costa et al. 2000, 2008; Costa 2007), competition with aggressive exotic species (Paula & Creed 2004, 2005; Creed 2006) and other human impacts (Leão et al. 1994; Leão & Kikuchi 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in fresh SGD and the unpredictable location of reduction could result in significant social consequences to its users (Moosdorf & Oehler, 2017) and aquatic species dependent on either the associated reduced salinity or nutrient delivery. Reduced nutrient fluxes would be disadvantageous in oligotrophic systems (e.g., Kim et al, 2011;Rodellas et al, 2015) but could also have a positive impact in eutrophic environments (e.g., Costa, 2007;Prouty et al, 2017;Redding et al, 2013).…”
Section: Implications For Offshore Fresh Groundwater Exploitationmentioning
confidence: 99%